194k views
0 votes
How would I solve for this?

How would I solve for this?-example-1
User Mvo
by
5.1k points

2 Answers

7 votes
Given question ,

f(x) = 5-x

As x is a function ,

Replacing value of x to find f(-7) by -7 gives us ,

f(-7) = 5-(-7)

f(-7) = 5 + 7

f(-7) = 12
User Madhivanan
by
5.6k points
2 votes

Answer:

1

Explanation:

replace x with -7

f(-7) = 5 - (-7)

f(-7) = 5 + 7

f(-7) = 12

User PTucky Eagle
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.